Thyroid-Mediated Metabolic Differences Underlie Ecological Specialization of Extremophile Salmonids in the Arctic Lake El’gygytgyn - Esin, Evgeny V.; Markevich, Grigorii N.; Zlenko, Dmitriy V.; Shkil, Fedor N. (Frontiers in Ecology and Evolution, 2021)
El'gygytgyn, the only 'ancient lake' in the Arctic (3.6 MY), is a deep (176 m) and extremely cold (always ≤ 4⁰C) waterbody inhabited by unique salmonids, which colonized the ecosystem stepwise during the global fluctuations of the Quaternary climate. The descendant of the first-wave-invaders (long-finned charr) dwells in the deep waters and feeds on amphipods. The second-wave-invaders (smallmouth charr) consume copepods in the mid-waters. Recent third-wave-invaders (Boganida charr) are spread throughout the ecosystem and feed on insects when they are young shifting to piscivory at an older age. Here, we present the data on the charrs’ thyroid status and metabolic characteristics, confirming their ecological specialization. The long-finned charr exhibits an extremely low thyroid content, the substitution of carbohydrates for lipids in the cellular respiration, an increased hemoglobin level and a high antioxidant blood capacity. These traits are likely to be the legacy of anaerobic survival under perennial ice cover during several Quaternary glaciations. Moderate thyroid status and reduced metabolic rate of the smallmouth charr, along with an inactive lifestyle, could be regarded as a specialization to saving energy under the low food supply in the water column. The piscivorous Boganida charr could be sub-divided into shallow-water and deep-water groups. The former demonstrates a significantly elevated thyroid status and increased metabolism. The latter is characterized by a reduced thyroid level, metabolic rate, and lipid accumulation. Thus, the endemic El'gygytgyn charrs represent a wide spectrum of contrast physiological adaptation patterns essential to survive in sympatry under extremely cold conditions.